OTS 2025 Sodobne informacijske tehnologije in storitve: Zbornik 28. konference, Maribor, 3. in 4. september 2025 (University of Maribor Press, 2025)
OTS 2025 Advanced Information Technologies and Services: Conference Proceeding of the 28th conference, Maribor, September 3th & 4th, 2025. In the proceedings of the twenty-seventh OTS 2025 conference, we find the IT experts contributions, in which new insights and trends in the development, implementation, adaptation and management of information systems are presented, as well as practical successful approaches and proven best practices. Contributions address the areas of architectural challenges, classical, generative, and deep artificial intelligence, modern webor mobile- user interfaces, as well as traditional, serverless and decentralized backend systems. The topics alsoinclude providing an appropriate scalable environment for them and automated testing, quality assurance and delivery by proactively addressing the most common cyber-attacks. One of the main topics remains data technologies in the form of classic databases, data lakes and efficient collection, processing, and big data visualisation. Contributions thus continue to enable a better connection between IT experts, informatics, architects and developers of advanced IT solutions and services, as well as the academia and industry.